THE CREATION OF NEW INFRASTRUCTURE UNITS OF THE RESEARCH ORGANIZATION - S. Ulanin (Publishing House of the State University of Management, 2017)
Article is aimed at creation of new infrastructure divisions of the research organization. Scientific organizations, especially branch accessory, have to have sufficient on structure and balance with the main functions of the organization infrastructure. An object of research is identification of missing infrastructure divisions of the research organization and their description. The results of a research given in article, including the retrospective analysis of license and patent activity, show demand of schools of sciences, departments of the international patent cooperation, the divisions rendering infrastructure services to the third-party organizations in the form of providing the ready results received by it on the basis of the unique equipment, a special set of scientific devices and the measuring equipment. In article the specific conditions characteristic of the research organizations necessary for formation of modern infrastructure are allocated.